2020
DOI: 10.2147/ott.s227644
|View full text |Cite
|
Sign up to set email alerts
|

<p>miR-939-5p Contributes to the Migration and Invasion of Pancreatic Cancer by Targeting ARHGAP4</p>

Abstract: Rho GTPase-activating protein 4 (ARHGAP4) is a GTPase-activating protein for the small GTPases of the Rho family that is involved in tumorigenesis. We recently reported that ARHGAP4 can mediate Warburg effect and malignant phenotype of pancreatic cancer. However, the regulation of ARHGAP4 remains unclear. Methods: ARHGAP4 and miR-939-5p expressions in pancreatic cancer tissues and cell lines were measured by real-time PCR or Western blotting. Pancreatic cancer cells were transfected with miR-939-5p inhibitor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…While cell biological studies on the function of ARHGAP4 were rather limited in number, there has been a significant increase of them in recent years. To date, almost all fundamental researches of ARHGAP4 have reported prominent functions in inhibiting cell migration and invasion (Shen et al, 2020;Vogt et al, 2007). Meanwhile, our study must be the first to our knowledge that revealed its molecular mechanism dominated by the SEPT2/9-driven modulation of FAs via its Rho-GAP and SH3 domains.…”
Section: Discussionmentioning
confidence: 75%
“…While cell biological studies on the function of ARHGAP4 were rather limited in number, there has been a significant increase of them in recent years. To date, almost all fundamental researches of ARHGAP4 have reported prominent functions in inhibiting cell migration and invasion (Shen et al, 2020;Vogt et al, 2007). Meanwhile, our study must be the first to our knowledge that revealed its molecular mechanism dominated by the SEPT2/9-driven modulation of FAs via its Rho-GAP and SH3 domains.…”
Section: Discussionmentioning
confidence: 75%
“…hsa-miR-939-5p, of potential interest for its role in invasive cancer, is reportedly upregulated in lung adenocarcinomas [43], hepatocellular carcinomas [44,45], ovarian cancer tissue [46] and in the promotion of blood vessel invasion in breast cancer [47]. The recent study by Shen et al [48] shed some light on the role of this hsa-miR-939-5p in PDAC biology and prognosis. By studying human pancreatic cancer tissues and cell lines, the authors demonstrated that high expression levels of this miRNA are associated with a poor prognosis in patients, while promoting in vitro tumor cell migration and invasion by targeting the Rho GTPase, activating protein 4.…”
Section: Discussionmentioning
confidence: 98%
“…Among the 39 PC-specific markers, 15 miRNAs have been reported to serve as PC markers in previous studies. Some of these (miR-155-5p, miR-939-5p, miR-346, miR-3064-5p, miR-661, miR-26a-5p, miR-200b-5p, and miR-218-5p) were found to be differentially expressed in PC tissues [15][16][17][18][19][20]23,24,27,[30][31][32]34,35,[37][38][39]. miR-939-5p, miR-200b-5p, and miR-218-5p were also differentially expressed in PC cell lines.…”
Section: Discussionmentioning
confidence: 99%